Sizing first flush pollutant loading of stormwater runoff in tropical urban catchments - Chow M.F.; Yusop Z. (Springer Verlag, 2023)
This study aimed at investigating the first flush phenomenon from residential, commercial and industrial catchments. Stormwater was grab sampled and the flow rate was measured during 52 storm events. The dimensionless cumulative pollutant mass and runoff volume were used to determine the runoff volume needed to transport 50 and 80 % of total pollutant mass. Almost all the constituents did not satisfy this first flush definition except for total suspended solids (TSS) in the commercial catchment. The averages first runoff volume required to remove 50 and 80 % of the total pollutant mass were 37 and 67, 35 and 65, and 36 and 64 % for the residential, commercial and industrial catchments, respectively. It seemed that less runoff is required to transport the same amount of pollutant loadings in tropical urban catchments than in temperate regions. BOD, COD, NH3-N, SRP and TP consistently showed strong first flush effects in all catchments. The first flush strengths of TSS, BOD, COD, NH3-N and TP in the commercial catchment were strongly correlated with total rainfall, rainfall duration, max 5 min intensity, runoff volume and peak flow, but not with antecedent dry days. Management of the first 10 mm runoff depth would be able to capture about half of the total pollutant mass in stormwater runoff that would otherwise goes to drains. © 2014, Springer-Verlag Berlin Heidelberg.